Breadth and Depth-Vocabulary Knowledge and Reading Comprehension in an English First Additional Language Context - Kufakunesu Zano (Journal of Languages and Language Teaching, 2022)
Most research has been concerned predominantly with vocabulary breadth in comparison with vocabulary depth. This study aims to bridge this gap by answering the following question: How do scores on vocabulary size, depth of vocabulary knowledge and reading comprehension correlate with each other? This study used quantitative method research on grade 11 English First Additional Language (EFAL) learners. Only 30 participants took part in the study. The independent variables used are the Vocabulary Levels Test (VLT) and Word Associate Test (WAT). Then, the dependent variable Reading comprehension is the dependent variable. The results indicated that 81% of the variance in the breadth of vocabulary scores which was measured through the VLT was shared with reading comprehension scores obtained in a reading comprehension test out of 30. On the other side, 90% of the variance in depth of vocabulary knowledge scores measured through a WAT was shared with reading comprehension scores. However, the depth of vocabulary scores could improve the prediction of the reading comprehension scores over and above the estimation accomplished by the vocabulary breadth scores. The results demonstrated the need for teachers to know their learners’ vocabulary knowledge and reading comprehension abilities.